2019
DOI: 10.1101/19010991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GBA variants in REM sleep behavior disorder: a multicenter study

Abstract: Objective: To study the role of GBA variants in the risk for isolated rapid-eye-movement (REM)-sleep behavior disorder (iRBD) and conversion to overt neurodegeneration. Methods: A total of 4,147 individuals were included: 1,061 iRBD patients and 3,086 controls. GBA was fully sequenced using molecular inversion probes and Sanger sequencing. We analyzed the effects of GBA variants on the risk for iRBD, age at onset (AAO) and conversion rates. Results: GBA variants were found in 9.5% of iRBD patients compared to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…This likely had a minimal effect on our results because mutations in the excluded exons in Europeans are rare. 17 Identification of complex alleles was also limited with our genotyping methods.…”
Section: Discussionmentioning
confidence: 99%
“…This likely had a minimal effect on our results because mutations in the excluded exons in Europeans are rare. 17 Identification of complex alleles was also limited with our genotyping methods.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The genetic background of iRBD has been only recently studied, with studies showing that there is no full genetic overlap between the genetic background of iRBD and that of PD or DLB. GBA mutations are associated with risk of iRBD, PD, and DLB, [11][12][13][14][15] but pathogenic LRRK2 mutations seem to be involved only in PD and not in iRBD and DLB. 7,16,17 MAPT and APOE variants are important risk factors of PD and DLB, respectively, 18,19 but both genes are not associated with iRBD.…”
Section: Comprehensive Analysis Of Familial Parkinsonism Genes Inmentioning
confidence: 98%
“…22 Within the TMEM175 locus, there are two independent risk factors of PD, but only one of them, the coding polymorphism p.M393T, has been associated with iRBD. 23 Here, because GBA and SNCA have been studied previously, 12,22 we aimed at thoroughly examining the roles of PRKN, PINK1, PARK7 (DJ-1), VPS13C, ATP13A2, FBXO7, PLA2G6, LRRK2, GCH1, and VPS35 in iRBD.…”
Section: Comprehensive Analysis Of Familial Parkinsonism Genes Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to examine the genetic basis of iRBD and its conversion, recent studies have examined whether PD- or DLB-associated genes are also associated with iRBD and whether they affect its conversion. It was demonstrated that while some genes such as GBA (Krohn et al, 2019b), TMEM175 (Krohn et al, 2019a) and SNCA (Krohn et al, 2019c) are associated with iRBD, other PD and DLB genes such as LRRK2 (Ouled Amar Bencheikh et al, 2018), APOE (Gan-Or et al, 2017) and MAPT (Li et al, 2018) are not. However, the association between SMPD1 and iRBD has not been investigated.…”
Section: Introductionmentioning
confidence: 99%